Upaya Penanggulangan Tindak Pelarian Narapidana untuk Meningkatkan Keamanan di Lapas Kelas IIA Abepura - Chrisostomus P.A. Kirwelakubun; Lauditta Indahdewi (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study examines the efforts to prevent inmate escapes at Class IIA Abepura Correctional Facility to enhance security. The research highlights the importance of correctional institutions not only in rehabilitating inmates but also in maintaining security and order. Despite the implementation of various rehabilitation programs, security challenges, particularly inmate escapes, persist. The study aims to evaluate current security measures, identify factors contributing to security weaknesses, and propose strategies for improving the prevention of inmate escapes at Class IIA Abepura. Using qualitative methods, the research gathers primary data through in-depth interviews with key personnel and inmates, alongside secondary data from relevant regulations and literature. The analysis provides insights into the effectiveness of current prevention efforts and suggests improvements in security systems, staff training, and operational protocols to ensure a safer correctional environment.